Strength–Ductility Trade-Off in Dual-Phase Steel Tailored via Controlled Phase Transformation - Srivastava, Ashok K.; Patel, Nand K.; Ravi Kumar, B.; Sharma, Ashutosh; Ahn, Byungmin (Journal of Materials Engineering and Performance, 2020)
The controlled phase transformation approach is a new generation of microstructure engineering for enhancing ductility in ultrafine-grained materials. The present study aims to extend this concept to dual-phase steel for enhanced tensile ductility at high strength. In this study, cold-rolled steel was subjected to annealing at different processing conditions to develop the core–shell microstructure constituting martensite core and ferrite as shell in the matrix. Controlled austenite decomposition was adopted in designing a core–shell-type structure. The evolved microstructure was characterized using a scanning electron microscope and electron backscatter diffraction technique. The results showed that the uniaxial tensile deformation of dual-phase structured steels had a remarkable strength–ductility trade-off. The ductility was increased anomalously at high martensite fractions. Further, the mechanism of damage activity leading to void nucleation and microcrack formation was studied in post-tensile fractured specimens to establish a correlation with tensile deformation characteristics. The possibility and outcomes of this approach are also reported here.
Keywords: Austenite decomposition; Electron backscatter diffraction technique; Microcrack formation; Microstructure engineering; Processing condition; Shell-type structures; Ultrafine grained materials; Uniaxial tensile deformation; annealing; core; dual phase; martensite; steel; tensile